The Effect of a Green Lifestyle on Organic Food Purchase Decisions Using the Behavioral Reasoning Theory Approach - I Kadek Adi Sanjaya Putra; Ni Wayan Eka Mitariani; I G NG A Gede Eka Teja Kusuma (International Journal of Accounting and Finance in Asia Pasific (IJAFAP), 2025)
The worsening environmental degradation has encouraged a shift in public behavior toward adopting a green lifestyle, which in turn affects consumption patterns, including decisions to purchase organic food. This study aims to analyze the influence of a green lifestyle on organic food purchasing decisions using the Behavioral Reasoning Theory (BRT) framework. A quantitative method was applied through a survey of 200 respondents knowledgeable about organic food, with data analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM). The results reveal that Reason For has a significant positive effect on purchase decisions (T = 4.467; p 0.001), indicating that stronger supporting reasons, such as health consciousness and environmental concern, enhance consumers’ likelihood of buying organic food. In contrast, Reason Against shows no significant effect (T = 0.856; p = 0.392), suggesting that barriers such as high prices or limited availability do not substantially discourage purchase intentions. These findings underscore the importance of emphasizing the positive value and sustainability aspects of organic products in marketing strategies to strengthen consumer engagement in green consumption behavior.